Spiritual Formation and Character Education: A Module Development for Christian Sunday School Children Based on Galatians 5:22–23 - Eudia Anggelia Ika Agustin; Hana Suparti; Muner Daliman (Pharos Journal of Theology)
This study aims to develop a character education module for Sunday school children rooted in Christian spiritual formation, using Galatians 5:22–23, the fruit of the Spirit, as its theological foundation. In response to the growing concern over moral development in children, especially in faith-based educational settings, the module integrates biblical principles with pedagogical approaches suitable for young learners. Employing the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation), the research includes a literature review, biblical exegesis, and field validation. The findings demonstrate that incorporating the fruit of the Spirit into structured Sunday school lessons significantly enhances the internalization of Christian virtues such as love, joy, peace, and self-control. This module offers a practical tool for teachers and church educators to nurture spiritual maturity and moral character in early childhood ministry. Theologically, it affirms the centrality of spiritual formation in Christian education and contributes to the discourse on faith-based curriculum development.